Applying parametric analysis in enhancing performance for double-layer scissor lifts - Dang, Anh-Tuan (Strojniški vestnik, 2023)
This study presents a calculation procedure of applying the statistical method in determining design parameters for double-layer scissor lifts to improve their operation (e.g., lifting height, loading, stability). By parameterizing the mounting orientation of cylinders, the working of the mechanism is summarized as functions and evaluated. To verify the accuracy of obtained equations, a 2D model of the mechanism was constructed and simulated using Working Model software. The results obtained from the simulation indicate that by adjusting the mounting positions of cylinders, the platform’s position and reactions on the device can be determined, enabling improvement of the system’s performance. The results obtained from the study show the practical significance of applying parametric methods to the calculating process and optimizing the structure of multiple-layer scissor lifts.
Keywords: cylinder’s orientation; double-layer scissor lift; dvoetažno škarjasto dvigalo; kinematic analysis; kinematična analiza; orientacija valjev; parametric method; parametrično konstruiranje